“In the same Boat” – Considerations on the Partnership between Healthcare Providers and Manufacturers of Health IT Products and Medical Devices - Bergh, B. (Yearbook of Medical Informatics, 2009)
Objectives To assess the current culture of cooperation between healthcare providers (HCPs) and the healthcare industry (HCI) in the domain of Health-IT and Engineering (HITE) and identify possible strategies for improvement.Methods Based on reports in the literature and personal experience, major challenges were identified, the current ways of cooperation defined and their relation to each other analyzed.ResultsFour main challenges were identified for both sides involving: products and functionality, integration of IT-Systems with each other and with medical devices, usability, visions and strategic management. None of the four defined cooperation categories cover all aspects of the challenges, but cooperation in small, dedicated groups appeared to provide the most advantages. An increased participation of HCPs in standardization activities is crucial either directly or indirectly via professional or scientific organizations.Conclusions Cooperation between provider management (hospitals, clinics or systems) and manufacturers of health IT products will be the key factor for success of the HCI while providing substantial benefits for providers. Both sides should invest heavily in such efforts.
Keywords: Cooperation; health-IT and medical engineering; public-private-partnership; standardization